Transition from youth categories to elite cycling: relationships between early career performance and UCI World Tour success - Cesanelli, L.; Ylaite, B.; Calleja-González, J.; Leite, N.; Iovane, A.; Messina, G. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: The present study aimed to describe the possible roles of cyclists` early career performance, on the transition process to elite cycling categories. METHODS: Data from national and international databases, and results achieved during the UCI World Championships, were retrospectively analyzed considering the Italian national Youth-U16, Junior-U18, and U23 categories, and international Junior-U18 and UCI World-Tour categories. RESULTS: The 15% of Youth-U16, the 38.8% of Junior-U18 and the 60% of U23 athletes who ranked top-10 between 2007 and 2013, scored points in UCI World Tour competitions between 2012 and 2018. The 1.6% of Youth-U16, the 8.3% of Junior-U18 and 25% of U23 athletes who ranked top-10 between 2007 and 2013, ranked among the Italian Top-10 in the UCI World-Tour individual classification between 2012 and 2018. Performance level in Youth-U16 category displayed a low correlation with UCI World Tour performance while the performance level in Junior-U18 category displayed a moderate correlation. The 34% of the Junior World Championship TOP-25 cyclists, participated in the elite competition. Trivial to small correlations emerged between Junior and elite World Championship performance levels. CONCLUSIONS: Early performance seems not to represent a good predictor of elite performance, while the Junior-U18 and the U23 performance level, emerged as potential indicators of future success in the elite categories.